Deformation‐Resilient Embroidered Near Field Communication Antenna and Energy Harvesters for Wearable Applications. (22nd August 2019) - Xu, Lulu; Liu, Zekun; Chen, Xiao; Sun, Rujie; Hu, Zhirun; Zheng, Zijian; Ye, Terry Tao; Li, Yi
Abstract : E‐Textiles have gained increasing momentum in wearable electronics recently. Conductive‐yarn‐based embroidered devices, with the advantages of being soft, deformable, breathable, and protective for the skin, play an important role in replacing many metallic counterparts. However, embroidered devices face many new challenges in their design methodology and fabrication processes, such as high resistivity and low Q value of the conductive yarns, as well as deformation of device geometries during wearing. Herein, a strain‐free, deformation‐resilient embroidery process for near field communication (NFC) coil antennas is introduced. Coil geometry can endure extreme deformation by stretching with up to 50% elongation, bending with curvature as small as 16 mm in radius, and can still maintain a relatively small variation in its inductance, resonant frequency, Q value, as well as its energy‐harvesting capabilities. The embroidered coil antenna is used in an NFC‐based battery‐free body sensor system. Experiments demonstrate that the system can maintain a stable performance (voltage supply, temperature sensing, and reading range) under various deformation conditions. Abstract : Herein, an embroidery process as well as deformation‐resilient designs are proposed for spiral coil structures that are resilient to deformation, while still maintaining good electromagnetic performance as near field communication (NFC)/radio‐frequency identification (RFID) antennas. This technique is used to build a complete NFC‐based energy‐harvesting "bra sensor, " as a wearable breast temperature–monitoring device.